2004
DOI: 10.1158/0008-5472.can-04-0073
|View full text |Cite
|
Sign up to set email alerts
|

External Beam Radiation of Tumors Alters Phenotype of Tumor Cells to Render Them Susceptible to Vaccine-Mediated T-Cell Killing

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
281
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(293 citation statements)
references
References 38 publications
8
281
1
3
Order By: Relevance
“…23 In addition to confirming some of these findings in this study using TRAMP-C1 cells, we further found that IL-3-induced Fas antigen expression, as did RT. The effect of RT is similar to recent findings by Chakraborty et al [5][6][7] They have proposed that radiationinduced tumor phenotype changes could enhance tumor cell susceptibility to antigen-specific CTL-mediated killing. The mechanism that mediates this type of phenotypic switch by IL-3 is still unclear.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…23 In addition to confirming some of these findings in this study using TRAMP-C1 cells, we further found that IL-3-induced Fas antigen expression, as did RT. The effect of RT is similar to recent findings by Chakraborty et al [5][6][7] They have proposed that radiationinduced tumor phenotype changes could enhance tumor cell susceptibility to antigen-specific CTL-mediated killing. The mechanism that mediates this type of phenotypic switch by IL-3 is still unclear.…”
Section: Discussionsupporting
confidence: 88%
“…As radiation-induced changes in MHC class I, ICAM-1, and Fas expression by tumor cells irradiated in vitro also have been reported [5][6][7] we examined expression of these molecules on TRAMP-C1 cells with and without Doxregulated IL-3 expression 4 h following a single in vitro dose of 0 or 7 Gy. Radiation was given 24 h after Dox treatment.…”
Section: The Influence Of Il-3 Gene Transfer and Radiation On Tumor Pmentioning
confidence: 92%
See 1 more Smart Citation
“…Sublethal doses of radiation up-regulated surface expression of Fas, ICAM-1, and MHC class I on tumor cells in a dose-dependent manner. In addition, destruction of the MC38-CEA tumors by this combination regimen was shown to be associated with a massive infiltration of tumor-specific CD8 + T cells [8].…”
Section: Vaccine and Radiationmentioning
confidence: 93%
“…To study this, the authors showed that radiation was able to improve the lytic sensitivity of tumor cells by TAA-specific CTL. A subsequent study [8] showed that irradiation-induced up-regulation of Fas on tumor cells could be combined with an active immunotherapy regimen. CEA-transgenic mice bearing MC38-CEA murine colon tumors were given priming vaccinations of recombinant vaccinia (rV) containing the transgenes for CEA and a triad of costimulatory molecules (B7.1, ICAM-1, LFA-3, designated TRICOM), followed by recombinant fowlpox (rF)-CEA-TRICOM booster vaccines.…”
Section: Vaccine and Radiationmentioning
confidence: 99%